Psychometric Properties of the Persian Version of the Love of Life Scale. Issue 2 (October 2016) - Vahid, Mohammad Kazem Atef; Dadfar, Mahboubeh; Abdel-Khalek, Ahmed M.; Lester, David
A love of life is defined as an overall positive attitude toward life and a liking for life. The present study was designed to evaluate the psychometric characteristics of a Persian version of the Love of Life Scale using a convenience sample of 145 Iranian female volunteer college students ( M age = 23.0 years, SD = 3.4). The mean score on the Love of Life Scale was 61.08 ( SD = 11.40). A principal component analysis with a Varimax rotation yielded two factors labeled (a) Positive Attitude Towards Life and Happy Consequences of Love of Life and (b) Meaningfulness of Life. Cronbach's alpha was .94 and the one-week test–retest reliability was .85. Love of Life Scale scores had significant positive correlations with scores on the Oxford Happiness Questionnaire, the Satisfaction with Life Scale, the General Self-Efficacy Scale, and the Adult Hope Scale. The scale displayed negative correlations with the Kessler Psychological Distress Scale and the Wish to be Dead Scale. It was concluded that the Persian form of the Love of Life Scale can be recommended for future research on positive psychology.